Pupil-centred spiritual leadership: an empirical study of thirteen church primary school headteachers in England - Eisl, Ursula; Woolley, Mary; Hulbert, Sabina; Casson, Ann; Bowie, Robert A. (International studies in Catholic education, 2025)
The place of Church school headteachers as spiritual leaders of the school community is rarely highlighted. This article investigates how 13 Church primary school headteachers (Catholic Church of England, and Methodist) interpret this role. It draws on the Faith in the Nexus research which investigated how church primary schools nurtured pupils' spiritual development and facilitated faith activity in the home. The head teacher interviews revealed several recurring themes, such as empowering children, collective worship, relationships with church and parents, and the visibility of faith in school. This research brings together a comparison of leadership approaches from Catholic and Anglican headteachers. Evidence of differences emerged; Catholic headteachers tended to use 'overtly religious' language while many Anglican headteachers employed a more 'secular' language to express their vision of spiritual leadership. A comparison with Shaw's ( 2015 , 2017) model of 'ethotic leadership', highlighted much in common. The headteachers' ethos was pupil-centric and shaped by a focus on the spiritual development of the child. An adaptation of Shaw's model is offered which places the child at the centre.